Processed multinet CTD data from METEOR cruise M133 - Michael Siccha; Michal Kucera (PANGAEA, 2018)
Research expedition M133 took place from December 15th, 2016 (Cape Town, South Africa) to January 13th, 2017 (Port Stanley, Falkland Islands). CTD data for 19 stations along the cruise track were recorded using a Sea & Sun Technology CTD90M (SN 979) down to depths of 700m. The CTD was equipped with the following sensors: Temperature sensor Pt100 model 1509 (Thermal Developments International), Conductivity sensor 7-pole platinum coated electrode cell in quartz glass (Sea & Sun Technology), Seapoint Chlorophyll Fluorometer (Seapoint) and single rod electrode ph sensor (AMT Analysenmesstechnik GmbH). The data files contain the data for temperature, salinity, density and chlorophyll a concentration and pH; as raw data and processed and flagged according to the recommendations for real-time data processing of EuroGOOS and GTSPP, as well as the outlier detection method CoTeDe (https://github.com/castelao/CoTeDe). Due to sensor malfunction/deterioration the pH data for the last four stations were excluded. Biogeographic regions are determined according to Spalding et al. (2012). TEOS-10 unit conversions have been performed with the GSW Oceanographic Toolbox (McDougall and Barker, 2011).